Post-mortem analysis of the deposit layers on the lower divertor after the 2023 high particle fluence campaign of WEST - C. Martin; M. Diez; E. Bernard; M. Cabié; A. Campos; C. Pardanaud; G. Giacometti; A. Gallo; J. Gaspar; Y. Corre; E.Tsitrone (Nuclear Materials and Energy, 2024)
We analysed deposits collected on the lower divertor of WEST after the first high fluence campaign performed in 2023. Deposits were collected on the high field side (thick deposition area) of 2 ITER-grade plasma facing units (PFUs), located on different toroidal positions. Using focused ion beam cross sectioning, the deposits were found to be very thick (12–55 µm). A significant difference was observed in the toroidal direction with thicker deposits for the PFU located at the maximal heat load in the inner side, showing a deposition pattern due to the toroidal magnetic field modulation. Deposits present a complex layer-by-layer structure with dense layers, some melted parts and porosities within the layers. The deposition is mainly composed of tungsten with oxygen, boron, carbon and traces of nitrogen whose composition vary along the radial direction. We identified W-rich deposits in the high plasma flux area near the inner strike point and deposits rich in O, B, C and N in the low plasma flux area further away from this strike point. W dense layers of about 5 up to 40 µm thick in the thick deposit area near the strike point were attributed to the high fluence campaign. Pure boron layers resulting from wall conditioning and processed by plasma wall interactions were also observed.